Transcription Factors Sp8 and Sp9 Regulate Medial Ganglionic Eminence-Derived Cortical Interneuron Migration - Tao, Guangxu; Li, Zhenmeiyu; Wen, Yan; Song, Xiaolei; Wei, Song; Du, Heng; Yang, Zhengang; Xu, Zhejun; You, Yan (Frontiers in Molecular Neuroscience, 2019)
Cortical interneurons are derived from the subpallium and reach the developing cortex through long tangential migration. Mature cortical interneurons are characterized by remarkable morphological, molecular, and functional diversity. The calcium-binding protein parvalbumin (PV) and neuropeptide somatostatin (SST) identify most medical ganglionic eminence (MGE)-derived cortical interneurons. Previously, we demonstrated that Sp9 plays a curial transcriptional role in regulating MGE-derived cortical interneuron development. Here, we show that SP8 protein is weekly expressed in the MGE mantle zone of wild type mice but upregulated in Sp9 null mutants. PV+ cortical interneurons were severely lost in Sp8/Sp9 double conditional knockouts due to defects in tangential migration compared with Sp9 single mutants, suggesting that Sp8/9 coordinately regulates PV+ cortical interneuron development. We provide evidence that Sp8/Sp9 activity is required for normal MGE-derived cortical interneuron migration, at least in part, through regulating the expression of EphA3, Ppp2r2c, and Rasgef1b.